KONSEP ARSITEKTUR RUMAH ADAT SUKU SASAK DI DUSUN SEGENTER, KECAMATAN BAYAN, LOMBOK UTARA – NTB - I Made Wirata; Ngakan Putu Sueca (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2014)
Abstract Traditional housing in Dusun Segenter deploys unique concepts in building structure, spatial pattern and architectural form. The house is organized based on the belief systems of the community, its norms and a sacred: profane orientation. The purpose of this study is to explain the concept of spatial patterns, shapes and facade forming the house of the Segenter. Phenomenology is used as the chosen qualitative method. Results of this study indicate that the main building site of Segenter village is based on traditions and customs that have been handed down from generation to generation by order of papuk baloq who is the head of the Village. The orientation and placement of the spaces in the main building like paon, amben beleq and klepok are based on the location of the door and the position of sakenem building. There is also an inan bale which is always located in the middle of the house. Both east-west and north-south orientation are also implemented in the Segenter's traditional house. The facade of the traditional building is the embodiment of the three main constituent elements - sacral value (reflecting the dominance of roof elements using inan bale construction; karang lamin; and its gable horns); orientation; and privacy. The material used is widely available around the village. The selected building material in use prioritizes consideration for comfort, adaptation to local climate, as well as accommodation for the functions and activities of residential space. Keywords:  spatial pattern, architectural concept, Sasak Ethnicity, traditional house, Dusun Segenter Abstrak Rumah adat Dusun Segenter memiliki konsep yang unik, baik dalam tata bangunan, pola ruangan dan bentuk arsitekturnya. Rumah adat ditata berdasarkan sistem kepercayaan, norma-norma setempat, serta orientasi sakral profan. Tujuan penelitian ini adalah untuk menemukan konsep pola keruangan, bentuk dan fasade rumah adat Dusun Segenter. Metode yang digunakan adalah metode kualitatif deskriptif dengan pendekatan fenomenologi. Hasil penelitian menunjukkan bahwa penataan dan penetapan lokasi bangunan utama rumah adat Dusun Segenter dilakukan berdasarkan tradisi yang diwariskan secara turun temurun atas perintah papuk baloq. Ruangan-ruangan yang ada di dalam bangunan utama yaitu paon, klepok dan amben beleq memiliki orientasi ruangan dan perletakan ruangan berdasarkan perletakan pintu dan letak bangunan sekenem, sedangkan inan bale selalu berada di tengah ruangan. Konsep sumbu timur-barat serta utara-selatan diterapkan di bangunan rumah adat Segenter. Tampak bangunan rumah adat merupakan perwujudan dari tiga unsur utama yang menonjol yaitu nilai kesakralan; orientasi; dan privasi. Nilai kesakralan dicerminkan dengan dominasi elemen atap yang terbentuk dari kontruksi inan bale, karang lamin serta gable horns dari bangunan rumah adat. Material yang digunakan adalah material yang banyak tersedia di sekitar desa. Pemilihan material bangunan mengutamakan kenyamanan, adaptasi dengan iklim setempat, serta pengakomodasian fungsi-fungsi ruang dan aktivitas di dalamnya. Kata kunci: pola ruang, konsep arsitektur, Suku Sasak, rumah adat, Dusun Segenter.